Indonesian Public Diplomacy: Preserving State Existence through Sharing of Indetities to Gain Mutual Understanding - Iva Rachmawati (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2017)
This article places public diplomacy as an effort to preserve state’s existence in the international relations as well as to share identity in order to achieve mutual understanding by state and non-state actors. The conception of public diplomacy over the years has placed public diplomacy on the narrow framework of the state’s efforts to build a positive image. As a result, such efforts are ignorant of the important efforts of non-state actors in building a fundamental thing for the existence of a state, its identity. Through some historical facts, this article shows that public diplomacy is an effort not only held by the state but also non-state actors in communicating their identity. Both actions are within the public diplomacy of state design or done independently. State domination sometimes limits the movement of non-state actors, but on the contrary in the current era of openness provides wider opportunities for non-state actors to play a better and more independent role in preserving their existence as well as relations among citizen